FINANCIAL MANAGEMENT IN THE FRAMEWORK OF SHARIA: EXPLORING THE BASICS OF FINANCIAL MANAGEMENT BASED ON ISLAMIC TEACHINGS - Izaty, Santi Nailul; Umairo, Tsania; Khadiqoh, Sabita; Aji, Gunawan; Andrean, Rizky (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Islamic financial management is a discipline that studies financial management according to Islamic sharia principles. This research is entitled Financial Management in the Framework of Sharia: Exploring the Basics of Financial Management Based on Islamic Teachings. This research aims to find out the Basics of Financial Management Based on Islamic Teachings within the framework of Sharia. This research uses a systematic literature review method to explore and analyze financial management in the framework of sharia by exploring the basics of financial management based on Islamic teachings. The results show that Islamic financial management focuses on the principles of justice, honesty, togetherness and compliance with Islamic law. The main principles include sharia compliance, maqashid sharia, prohibition of usury, justice, taawun, benefit, and balance. Its scope includes Islamic financial institutions such as banks, capital markets, insurance, and other financing institutions. Its functions include sharia-compliant funding, investment, and profit sharing/dividend decisions. Challenges include capitalization, product development, human resources, infrastructure, instrument variability, and the application of sharia principles. And Islamic financial management offers a more stable and sustainable approach by taking into account the spiritual and ethical aspects of financial management. However, with continuous innovation and consistent application of sharia principles, sharia financial management can contribute to creating a financial system that is more stable, sustainable and beneficial to the wider community